Regional homogeneity alterations of resting-state functional magnetic resonance imaging of chronic rhinosinusitis with olfactory dysfunction - Zhiqiang Zhang; Ying Wu; Qing Luo; Junhao Tu; Jiahao Li; Jiaxin Xiong; Huiting Lv; Jing Ye (Frontiers in Neuroscience, 2023)
ObjectivesThe aim of this study was to assess the brain functional changes of patients with chronic rhinosinusitis with olfactory dysfunction (CRSwOD) using regional homogeneity (ReHo) of resting-state functional magnetic resonance imaging (MRI) scans, and to better explain the occurrence and development of olfactory decline in patients with chronic sinusitis provides a new idea for the study of more advanced olfactory therapy modalities.MethodsA total of 28 CRSwOD patients, 24 patients with CRS without olfactory dysfunction (CRSsOD), and 25 healthy controls (HCs) were recruited. All subjects underwent olfactory testing, clinical and brief psychological assessments, and MRI scans. A two-sided two-sample t test with AlphaSim correction (voxel-p < 0.001, cluster size >54 voxels) was used to detect differences between CRSwOD, CRSsOD, and HC groups.ResultsCompared with HCs, the ReHo values in traditional olfactory regions (e.g., parahippocampal gyrus (PHG), hippocampal, olfactory cortex) were increased, and ReHo values in the frontal gyrus, middle temporal gyrus, precuneus, and posterior cingulate gyrus were decreased in CRSwOD patients. The ReHo values in the precuneus and posterior cingulate gyrus of CRSwOD patients were negatively correlated with Questionnaire of Olfactory Disorders-Negative Statements (QOD-NS) scores. Compared with CRSsOD patients, the ReHo values in cerebellar regions were increased and those in the inferior temporal gyrus, precuneus, postcentral, and paracentral gyrus were decreased in CRSwOD patients. The receiver operating characteristic (ROC) curve showed that the mean ReHo values significantly differed between the CRSwOD and CRSsOD groups.ConclusionSynchronization of regional brain activity in the regions of the secondary olfactory cortex orbitofrontal cortex (OFC), temporal gyrus, precuneus, and cerebellum may be closely related to the development of olfactory dysfunction. Precuneus and posterior cingulate gyrus may be critical brain areas of action for emotional dysfunction in CRSwOD patients.